Q. 14.3( 145 Votes )

Find the roots of

Answer :

Here, on comparing with general equation ax 2 + bx + c = 0, we get

a = 1

b = - 3

c = - m(m + 3)

Now, Discriminant = D = (b2 – 4ac)

D = [9 -4 × (-m(m + 3))]

= [9 + 4m2 + 12 m]

= (2m + 3)2

Therefore roots of the equation are given by:

x = (-b ± √D)/2a

x = (3 ± (2m + 3))/2

= [(6 + 2m)/2] or [-2m/2]

= 3 + m or – m.

Thus the roots of the equation are: - m and m + 3.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses